A new species of Tetragonopterus Cuvier, 1816 (Characiformes, Characidae, Tetragonopterinae) from the upper rio Araguaia, Central Brazil - Silva, Gabriel S. C.; Benine, Ricardo C. (Zootaxa, 2011)
A new characid, Tetragonopterus anostomus, is described from the upper rio Araguaia, Central Brazil. The new species is distinguished from its congeners (T. argenteus, T. carvalhoi, T. chalceus e T. rarus) by traits related to the position of the mouth, number of premaxillary teeth, number of predorsal scales, overall color pattern, and number of gill rakers. A brief discussion on its putative ecomorphological adaptations is provided.